2019
DOI: 10.3847/1538-4357/ab4f7b
|View full text |Cite
|
Sign up to set email alerts
|

Reverberation Measurements of the Inner Radii of the Dust Tori in Quasars

Abstract: We present the results of a dust-reverberation survey of quasars at redshifts z < 0.6. We found a delayed response of the K-band flux variation after the optical flux variation in 25 out of 31 targets, and obtained the lag time between them for 22 targets. Combined with the results for nearby Seyfert galaxies, we provide the largest homogeneous collection of K-band dust-reverberation data for 36 type 1 active galactic nuclei (AGNs). This doubles the sample and includes the most distant AGN and the largest lag … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 115 publications
2
83
0
Order By: Relevance
“…In the last 20 years, a number of dedicated dust reverberation campaigns have substantially increased the sample of lags (e.g., Suganuma et al., 2006 ; Koshida et al., 2014 ; Minezaki et al., 2019 ), as have surveys with repeated imaging that search for transient phenomena ( Lyu et al., 2019 ; Yang et al., 2020 ), firmly establishing the dust relation over 4 orders of magnitude in luminosity. On average, the dust lags are 4 times longer than Hβ lags (e.g., Koshida et al., 2014 ; Netzer 2015 ; see Figure 10 for a comparison of dust and BLR radii), demonstrating that the bulk of the BLR is enclosed within the dusty torus, as expected from AGN unification arguments.…”
Section: Dust Reverberation and Beyondmentioning
confidence: 99%
“…In the last 20 years, a number of dedicated dust reverberation campaigns have substantially increased the sample of lags (e.g., Suganuma et al., 2006 ; Koshida et al., 2014 ; Minezaki et al., 2019 ), as have surveys with repeated imaging that search for transient phenomena ( Lyu et al., 2019 ; Yang et al., 2020 ), firmly establishing the dust relation over 4 orders of magnitude in luminosity. On average, the dust lags are 4 times longer than Hβ lags (e.g., Koshida et al., 2014 ; Netzer 2015 ; see Figure 10 for a comparison of dust and BLR radii), demonstrating that the bulk of the BLR is enclosed within the dusty torus, as expected from AGN unification arguments.…”
Section: Dust Reverberation and Beyondmentioning
confidence: 99%
“…This emission is attributed to dust that has been heated to its sublimation temperature by the central continuum source (Rees et al 1969;Rieke 1978;Barvainis 1987). Interferometric observations (Kishimoto et al 2009(Kishimoto et al , 2011Gravity Collaboration et al 2020) confirm that the emission from the shortest-wavelength components of the nearinfrared excess is located close in to the central continuum source, while reverberation mapping studies have shown that the hot dust is located just outside the broad emission line region (BLR), perhaps even setting the outer limit of that region (Suganuma et al 2006;Goad et al 2012;Landt et al 2019;Minezaki et al 2019).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, Suganuma et al (2006) search for time delays between the optical and NIR (J, H, K) bands in three additional sources, also finding much longer time delays: NGC 5548: 47-53 d; NGC 3227: ∼20 d; NGC 7469: 65-87 d. Meanwhile, further dedicated dust-reverberation campaigns and imaging surveys (e.g. Koshida et al 2014;Lyu, Rieke & Smith 2019;Minezaki et al 2019;Yang et al 2020) continue to build up a large sample of long, correlated time delays from the distant, toroidal structures that surround AGN (also see Netzer 2015). Such results help to build up evidence for a picture in which accretion-disc gas may extend out to ∼12 light-days, while continuum-band lags may be observed with significantly longer time delays, relative to the black-hole mass of the source.…”
Section: Discussionmentioning
confidence: 99%